Pedagogia crítica, educação/educação física e o ensino de pessoas com deficiência intelectual - Pagotto, Fernanda Pires (2010)
This research aimed to investigate and analyze the contributions of the critical theories of Education and Physical Education for teaching children with intellectual dificiency in a special school. A qualitative approach was adopted, characterized as case study with approximations ethnos. Was realized a field study in six months in a class of 13 children in school age, commited between 8 and 13 years, a special school of the city of Vitória, Espírito Santo. The empiric data allowed to analyse limits, possibilities and challenges found in the physical education teaching based by beginnings common to the theories criticize